Cambridge primary English Learner's book 6 - Burt, Sally (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Learner's Book 6 is designed to help students in their final year of primary education build on and refine their English language skills. It focuses on enhancing proficiency in reading, writing, listening, and speaking, preparing students for secondary education. The book aligns with the Cambridge Primary English curriculum and provides a range of engaging activities and exercises.
Keywords: English : Textbook